Clinical use and toxicities of bortezomib in pediatric patients: a systematic review - Zachary C. LeBlanc; Averill Clapp; Samantha Kaplan; Carrie J. Shawber; Carrie J. Shawber; June K. Wu (Frontiers in Pharmacology)
BackgroundProteasome inhibitors (PIs) are FDA-approved to treat adult malignancies. The PI, Bortezomib (BTZ), has been used off-label in pediatric patients but its safety profile in these patients has yet to be systematically assessed. We sought to review the pediatric safety profile of BTZ based on published clinical articles which we compared to publicly available adult safety data from the BTZ drug insert.MethodsPubMed and the Cochrane Database were searched up through September 2024. We included published clinical studies that reported adverse events (AEs) which included clinical trials, clinical studies (>10 patients), and clinical series/case reports (≤10 patients). Extracted pediatric safety data was compared to reported adult safety profile from the BTZ drug insert.ResultsThere was heterogeneity in reporting of different AEs and not all categories were comparable to published adult AEs.any studies were small case series or reports which did not allow for more quantitative analysis. Nevertheless, we found that pediatric patients treated with BTZ reported lower incidence of peripheral neuropathy and gastrointestinal toxicity compared to adults. Rates of bone marrow suppression and infection in pediatrics were comparable to or higher than those observed in adults These incidences were comparable or lower when pediatric patients with leukemia were excluded.DiscussionBTZ has an acceptable safety profile for use in pediatric patients. Antibacterial and antifungal prophylaxis should be considered given the high rate of infections.